Cross-Level Influence of Empowering Leadership on Constructive Deviance: The Different Roles of Organization-Based Self-Esteem and Traditionality - Wang, Yanzi (Frontiers in Psychology, 2022)
At present, scholars have mainly focused on the individual-level influencing factors of constructive deviance, and few studies have concerned the motivating mechanism of empowering leadership on constructive deviance. Based on the conservation of resources theory, this study explored the cross-level influence of empowering leadership on constructive deviance. With the data of 85 leaders and 383 paired employees which were collected in two waves with one-month time lag, the results demonstrated that empowering leadership motivated employees to actively implement constructive deviance, and that organization-based self-esteem played a mediating role in the relationship. The high traditionality of employees weakened not only the positive effect of organization-based self-esteem on constructive deviance, but also the mediating role of organization-based self-esteem. This study lays a theoretical basis and provides some practical guidance for leaders to take effective empowerment strategies to motivate employees to engage in constructive deviance.